2018
DOI: 10.1177/0956462418788432
|View full text |Cite
|
Sign up to set email alerts
|

Urinary liver-type fatty acid-binding protein levels as a potential risk factor for renal dysfunction in male HIV-infected Japanese patients receiving antiretroviral therapy: a pilot study

Abstract: Renal dysfunction is recognized with increasing frequency among the non-infectious co-morbidities associated with human immunodeficiency virus (HIV) infection. Recently, urinary liver-type fatty acid-binding protein (L-FABP) was suggested to be a predictor of the progression of renal dysfunction in patients without HIV. However, little is known regarding the utility of urinary L-FABP as a predictor of renal dysfunction in patients with HIV. A retrospective, observational, single-centre study was conducted betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Although UL-FABP level was suggested to be a potential predictor of renal dysfunction [4], availability of UL-FABP level in patients with low Uβ2MG level remains unclear. To our knowledge, this is the first study that showed the usefulness of UL-FABP in predicting eGFR decrement in patients receiving TDF with low Uβ2MG levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although UL-FABP level was suggested to be a potential predictor of renal dysfunction [4], availability of UL-FABP level in patients with low Uβ2MG level remains unclear. To our knowledge, this is the first study that showed the usefulness of UL-FABP in predicting eGFR decrement in patients receiving TDF with low Uβ2MG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into two groups according to UL-FABP levels of 4.0 μg/g creatinine based on the previous study [4]. Kaplan-Meier analysis and a log-rank test were then performed to estimate the effect of UL-FABP on time to the end points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] It has been suggested that urinary levels of L-FABP may be a predictor of renal outcomes in patients with and without HIV. [11][12][13][14][15] It is unknown whether the switch from TDF to TAF improves urinary levels of L-FABP, although in clinical trials comparing TAF-and TDF-based regimens, it was demonstrated that this switch improved proteinuria and urinary levels of b2MG. [16][17][18][19][20] Thus, the primary aim of the present study was to assess the change in urinary levels of L-FABP after this change in medication.…”
Section: Introductionmentioning
confidence: 99%
“…810 It has been suggested that urinary levels of L-FABP may be a predictor of renal outcomes in patients with and without HIV. 1115…”
Section: Introductionmentioning
confidence: 99%